Engaging homeless individuals in discussion about their food experiences to optimise wellbeing: A pilot study. (August 2017) - Pettinger, Clare; Parsons, Julie M; Cunningham, Miranda; Withers, Lyndsey; D'Aprano, Gia; Letherby, Gayle; Sutton, Carole; Whiteford, Andrew; Ayres, Richard
Objective: High levels of social and economic deprivation are apparent in many UK cities, where there is evidence of certain 'marginalised' communities suffering disproportionately from poor nutrition, threatening health. Finding ways to engage with these communities is essential to identify strategies to optimise wellbeing and life skills. The Food as a Lifestyle Motivator project aimed to pilot creative methods among homeless adults for the examination of food-related experiences in order to facilitate their engagement in the wellbeing discourse. Design: Creative Participatory Action Research methods including Photo-Elicitation. Setting: A homeless service provider in Plymouth, UK. Method: A sample of homeless service users took photographs of their food activities over a 10-day period, and then volunteered to share their photos in focus group discussions to elicit meaning related to their food experiences. Results: Five themes were generated from nine service user narratives, demonstrating that food holds meaning, elicits emotions and exerts power. The food environment can be a critical social meeting place and food preparation can provide companionship and occupation. Conclusion: As well as being central to many health concerns, food may also be a powerful way to motivate people to change their lifestyle. The participatory methods used in this pilot hold potential to engage effectively with harder-to-reach service users. Discussions about their wellbeing indicate food as a powerful 'catalyst' for inclusion with the potential to empower individuals. The study serves to inform health education practice, design of services and address (nutritional) health inequalities.